The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1093/rpd/nct095
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on an automatic computed tomography tube current modulation system

Abstract: The scope of this study was to evaluate the effects on radiation output and image noise varying the acquisition parameters with an automatic tube current modulation (ATCM) system in computed tomography (CT). Chest CT examinations of an anthropomorphic phantom were acquired using a GE LightSpeed VCT 64-slice tomograph. Acquisitions were performed using different pitch, slice thickness and noise index (NI) values and varying the orientation of the scanned projection radiograph (SPR). The radiation output was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…This is in accordance with one previous study 15 and contrary to another that found that the two were equivalent. 13 It is owing perhaps to the smaller projected area of the CT table, although it has also been suggested that the greater magnification of the spine in the PA view plays a role.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with one previous study 15 and contrary to another that found that the two were equivalent. 13 It is owing perhaps to the smaller projected area of the CT table, although it has also been suggested that the greater magnification of the spine in the PA view plays a role.…”
Section: Discussionsupporting
confidence: 93%
“…13 It is owing perhaps to the smaller projected area of the CT table, although it has also been suggested that the greater magnification of the spine in the PA view plays a role. 15 The 90°localizer angle was found to offer lower radiation output than did both 0°and 180°localizer angles. Again there is no consensus among previous research for this finding, with studies that both corroborate it 12,13 and find the contrary.…”
Section: Discussionmentioning
confidence: 88%
“…The way certain scan settings affect the ATCM from different vendors has been an area of interest for many years. 3,[5][6][7][8][9][10][11][12] The focus has been on the effect of a limited number of scan settings or on a specific vendor ATCM. However, an extensive study investigating the influence of all variable scan settings and covering all of the vendor implementations of ATCM is, to our knowledge, missing in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that at noise index values of 18-25 HU, the quality of CT images sufficed for diagnostic purposes in abdomen [17,18]. Moro et al reported that the range of noise indexed in chest was 10 to 25 HU [19]. Therefore, in the current study, the noise index values were chosen as either 21 HU, the default value of the scanner, or 25 HU, the upper limit reported in literature.…”
Section: Aecmentioning
confidence: 89%